Association between temporomandibular disorders and pubertal development: A systematic review. (8th September 2018) - Song, Yi Lin; Yap, Adrian U.; Türp, Jens C.
Summary: The aim of this systematic review (SR) was to determine the association between temporomandibular disorders (TMDs) and pubertal development. Due to the inadequacy of the conventional PICO (Population, Interventions, Comparisons and Outcome) format used for intervention‐based SRs, the Joanna Briggs Institute's guidelines for synthesising evidence related to associations with a focus on aetiology were adopted. A search of the PubMed and LIVIVO databases covering the period from January 1980 to May 2018 yielded four publications, which fulfilled the inclusion criteria. Analysis of articles based on the Pubertal Development Scale showed that TMD prevalence increases with pubertal development. Although no sex difference in TMD prevalence and diagnosis was observed, more females reported TMD anamnestic variables, including accounts of temporomandibular pain during pubertal maturity. The higher prevalence of depression and somatisation during pubertal development may contribute to more TMD symptom reporting in females. More prospective studies incorporating standardised methods for diagnosing TMDs and detecting comorbid psychosocial and somatic problems are desired to further elucidate the relationship between TMDs and pubertal development.